PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 009 BINIO JAYA KECAMATAN KELAYANG - ', Lasmita; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed purpose of this research is to improve learning outcomes IPA students class fourth of SDN 009 Binio Jaya Kecamatan Kelayang by applying the learning model NHT. The subjects were students of class IV consisting 24 students consisting of 13 male students and 11 female students. This type of research is the Classroom Action Research (PTK), which comprises two cycles (4 meetings). Based on the research activities of teachers in the first cycle-one meetings to gain success 58.33% with less criteria. At the 2nd meeting increased to 70.83% with good criterion. In the second cycle to meeting all first gained 83.33% success criteria very well. At the 2nd meeting increased to 91.67% with the criteria is also very good. Activities of students in the first cycle-one meetings to gain success with krieria 45.83% less. 2nd meeting increased to 62.5% with sufficient criteria. Implementation of the second cycle of meetings to-1 increased to 83.33% with good criterion once. At the 2nd meeting increased to 91.67% with good criterion once. The average value of daily tests before deploying IPA student cooperative learning model NHT is 63.54. At UH 1 daily value increased to 67.92 students who have increased as much as 6.89% by the number of students who completed 9 students from 24 students. At UH 2 has increased the average value of as much as 34.76% to 85.63. It can be concluded that the application of cooperative learning model NHT can improve learning outcomes IPA students class fourth of SDN 009 Binio Jaya Kecamatan Kelayang.Â Keywords: Cooperative Learning NHT Model, Â Learning Outcomes IPA .